Necesidad de Establecer una Jornada Laboral a los Concejales por ser Considerados de Acuerdo a Ley Servidores Públicos - Carriòn Guarderas, Cristopher Gualberto (2018)
The present thesis entitled: "Need to establish a working day for the Councilors to be considered according to law public servants", is based on the benefits of law granted by the State Councilors for having included them within public servants, that is to say a monthly salary, Social Security affiliation, liquidation, tenth and fourteenth remuneration, vacations, which in times prior to the 2008 Constitution did not have because that dignity of popular election was considered an honorary position, but only were dietary creditors because of the sessions that the council had during the month, the key foundation of this investigation is that as well as they are worthy of all the benefits of law that are guaranteed to public servants, the municipal councilors must comply with a working day as the law stipulates in the obligations of the Public Servants, it is established that the Aldermen only must be governed by the Organic Code of Territorial Organization Autonomy and Decentralization (COOTAD) and what the Constitution stipulates, therefore it is necessary to set fair precepts in the Organic Code of Territorial Organization Autonomy and Decentralization based on municipal classification and the scale of ceilings and floors of the monthly remunerations of the and the servants of the Autonomous Decentralized Municipal Governments that the Ministry of Labor determines, for the creation of the Ordinance of Operation of the Municipal Council. Art. 11 numeral 2 of the Constitution of the Republic states All people are equal and will enjoy the same rights, duties and opportunities, that is, there should be no labor 5 preferences, since they are within the same categorization and have the same The same benefits must therefore comply with the obligations as such among the main ones is the execution of their activities through a working day, for the different attributions that the law grants to the Councilors it is established that the ordinance must be created according to the jurisdiction territorial and the activities carried out as a municipality based on the categorization of the Ministry of Labor. The theoretical, legal and doctrinal collection, the application of surveys and interviews, allowed to obtain criteria with clear and precise foundations, of highly recognized bibliography, which contributed to the verification of the objectives and to the testing of the hypothesis raised regarding this practice; both the Constitution of the Republic of Ecuador and the Organic Code of Territorial Organization, Autonomy and Decentralization, which are the only ones that stipulate the attributions of duties and rights of the municipal EdIles